Detection of Antiviral Tissue Responses and Increased Cell Stress in the Pancreatic Islets of Newly Diagnosed Type 1 Diabetes Patients: Results From the DiViD Study - Krogvold, Lars; Leete, Pia; Mynarek, Ida M.; Russell, Mark A.; Gerling, Ivan C.; Lenchik, Nataliya I.; Mathews, Clayton; Richardson, Sarah J.; Morgan, Noel G.; Dahl-Jørgensen, Knut (Frontiers in Endocrinology, 2022)
Aims/hypothesis: The Diabetes Virus Detection (DiViD) study has suggested the presence of low-grade enteroviral infection in pancreatic tissue collected from live adult patients newly diagnosed with type 1 diabetes (T1D). The present study aimed to compare the gene and protein expression of selected virally induced pathogen recognition receptors and interferon stimulated genes in islets from these subjects vs age-matched non-diabetic (ND) controls. Methods: RNA was extracted from laser-captured islets and Affymetrix Human Gene 2.0 ST arrays used to obtain gene expression profiles. Lists of differentially expressed genes were subjected to a data-mining pipeline searching for enrichment of different pathways and regulators. The presence and localisation of specific viral response proteins were examined by combined immunofluorescent labelling in sections of pancreatic tissue. Results: The data mining process revealed a significant enrichment of several gene ontologies and KEGG pathways covering viral reproduction and infectious cycles; peptide translation, elongation and initiation, as well as oxidoreductase activity. Protein Kinase R (PKR) expression did not differ between newly diagnosed type 1 diabetes and ND islets at the level of total RNA, but a subset of β-cells displayed increased PKR protein levels. These PKR+ β-cells correspond to those previously shown to contain the viral protein, VP1. RNA encoding MDA5 was increased significantly in T1D islets, and immunostaining of MDA5 protein was seen in α- and certain β-cells in both T1D and ND islets, but the expression was increased in β-cells in T1D. In addition, an uncharacterised subset of synaptophysin positive, but islet hormone negative, cells expressed intense MDA5 staining and these were more prevalent in DiViD cases. MxA RNA was upregulated in T1D vs ND islets and MxA protein was detected exclusively in T1D β-cells. Conclusion/interpretation: The gene expression signatures reveal that pathways associated with cellular stress and increased immunological activity are enhanced in islets from newly diagnosed T1D patients compared to controls. The increases in viral response proteins seen in β-cells in T1D provide clear evidence for the activation of IFN signalling pathways. As such, these data strengthen the hypothesis that an enteroviral infection of islet β-cells contributes to the pathogenesis of T1D.